Pontos de conflito na relação criança-escrita e seus efeitos heterogêneos: rasuras, reformulações, recomposições textuais - Pires, Vera Lucia (2015)
This research focuses on the tense relationship between children and their own writing skill at school. Reading and writing are intermingled and simultaneous through the literacy process, though not coincident in their effects. The expression "tense relationship" here adopted disclaims any possibility of taking for granted that writing skills would undertake a natural trend, i.e., free from deep conflict, once the child is already a "language speaker . This argument seems not to be sustained by the serious and enigmatic problems the child has when s/he has to deal with the teaching-learning of her/s mother tongue. True enough, the effects of mentioned tension student-writing has a heterogeneous profile, which can be apprehended through the multifaceted ways of reformulating one s writings: different erasure markings and/or internal sequential unstable text rearrangements. In this sense, the present dissertation dealt with such occurrences, both from an empirical and a theoretical approach, taking into account the two initial years of Brazilian School, named Fundamental II. At such a stage, it is expected that students writings are better stabilized and with few errors. Those unwilling manifestations, from the teachers point of view, indicate that the writer has been affected by he/s own writing. This seems to be a crucial turning point in the learning process, since s/he may overcome her/s difficulty or, worse, get stuck in a doing-redoing task. From the theoretical perspective regarding language, this study is assumes the European Structuralism scientific proposal (SAUSSURE, 1916) and (JAKOBSON, 1954;1960) and follows J-C Milner s approach to those authors, and also the developments put forward by Cláudia de Lemos in the realm of Language Acquisition and Lier-DeVitto in the field of Language Pathology and Clinic. The theoretical option for that structural approach is due to the relevance they place in error, which questions the psychological subject and favors the hypothesis of the unconscious, introduced by Freud (1900). It is understood here that such a theoretical framework sheds light on the literacy process, since tension and conflict are constitutive moves in the subject-language relationship. There are three proposed structural shifts which are qualified as the child s changing of position as far as language acquisition is concerned. The child s starting point has to do with her/s (1) attachment (dependency) to the others oral or written production. In a given structural logical moment, (2) the functioning of language itself operates on the incorporated segments, producing errors and strange textual composition, which are listened to (3) when the subjective split takes place (a division between an instance who hears and another who speaks), allowing for the listening to one s own speech/writing. This is the most relevant structural position for the present study, which discusses erasures and textual rearrangements in the sphere of the child-writing relationship